The Effect of LDPE Micropastics in the Blood on Leydig Cell Damage, Sertoli Cell Damage, and Sperm Count in the Male Wistar Rats - Shallom Emmanuella Milanisty; Irene Lingkan Parengkuan; Edwin Budipramana; Yudhiakuari Sincihu; Harnoprihadi Noorlaksmiatmo (ECOTON: Ecological Observation and Wetlands Conservation, 2026)
Low-density polyethylene (LDPE) microplastics are increasingly detected in the environment and can enter the human body through ingestion or inhalation. Microplastic exposure is associated with oxidative stress, inflammation, and cellular injury that may impair male reproductive health. Leydig and Sertoli cells play essential roles in spermatogenesis; therefore, damage to these cells can reduce sperm production and quality. However, evidence regarding the effects of LDPE microplastics on testicular morphology and spermatogenesis is still limited. This research aims to determine the effects of oral LDPE microplastic exposure on Leydig cell injury, Sertoli cell injury, and sperm count in male Wistar rats. This true experimental study used a post-test only control group design. Rats were divided into control and LDPE-treated groups. Testicular histopathology was evaluated, and data were analyzed using the Kruskal–Wallis test, Levene’s test, and Spearman correlation. LDPE exposure caused degenerative changes in Leydig and Sertoli cells and significantly reduced sperm count (p < 0.001). Oral LDPE microplastic exposure induces testicular cell damage and decreases sperm count, indicating potential reproductive toxicity.